2009
DOI: 10.5194/angeo-27-4505-2009
|View full text |Cite
|
Sign up to set email alerts
|

Melting of major Glaciers in the western Himalayas: evidence of climatic changes from long term MSU derived tropospheric temperature trend (1979–2008)

Abstract: Abstract. Global warming or the increase of the surface and atmospheric temperatures of the Earth, is increasingly discernible in the polar, sub-polar and major land glacial areas. The Himalayan and Tibetan Plateau Glaciers, which are the largest glaciers outside of the Polar Regions, are showing a large-scale decrease of snow cover and an extensive glacial retreat. These glaciers such as Siachen and Gangotri are a major water resource for Asia as they feed major rivers such as the Indus, Ganga and Brahmaputra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 54 publications
(62 reference statements)
1
81
0
1
Order By: Relevance
“…Rosenfeld et al, 2001;Gautam et al, 2009a;Prasad et al, 2009;Anton et al, 2011;Christopher et al, 2011;Valenzuela et al, 2012).…”
Section: Introductionunclassified
“…Rosenfeld et al, 2001;Gautam et al, 2009a;Prasad et al, 2009;Anton et al, 2011;Christopher et al, 2011;Valenzuela et al, 2012).…”
Section: Introductionunclassified
“…The ABC can be even 3-km thick and can be transported several kilometers downwind, affecting south India and the adjoining oceanic regions (Ramanathan et al, 2005). Furthermore, they absorb the solar radiation heating the atmosphere, thus causing a temperature anomaly over northern India (Gautam et al, 2010) able to cause the melting of the Himalayan glaciers (Prasad et al, 2009;Menon et al, 2010).…”
Section: Aerosol and Pollution Transport Over Bobmentioning
confidence: 99%
“…Lal and Singh (2001) and Lal (2001) have reported that the average annual mean surface temperature over Indian sub-continent is likely to increase by about 2.7 and 3.8 °C during the decades of 2050 and 2080 s, respectively. Dyurgerov and Meier (2005) and Prasad et al (2009) mentioned that in recent years, the glaciers and snowfields of the Himalaya-KarakoramHindu Kush (HKH) mountain belts and Tibetan plateau are found to be amongst the fastest receding glacial and snow covers in the world. Again, Kulkarni et al (2007) and Raina (2009) said that the simultaneous fragmentation of the glaciers along with glacial retreats has also degraded the total areal coverage of perennial snow and ice in the HKH region.…”
Section: Introductionmentioning
confidence: 99%